2023
DOI: 10.1001/jama.2022.24162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Concentration Atropine Eyedrops vs Placebo on Myopia Incidence in Children

Abstract: ImportanceEarly onset of myopia is associated with high myopia later in life, and myopia is irreversible once developed.ObjectiveTo evaluate the efficacy of low-concentration atropine eyedrops at 0.05% and 0.01% concentration for delaying the onset of myopia.Design, Setting, and ParticipantsThis randomized, placebo-controlled, double-masked trial conducted at the Chinese University of Hong Kong Eye Centre enrolled 474 nonmyopic children aged 4 through 9 years with cycloplegic spherical equivalent between +1.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
57
1
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 41 publications
2
57
1
3
Order By: Relevance
“…Methods evaluated include multifocal contact lenses, orthokeratology, and low-dose atropine eyedrops, which have had the most attention in randomized clinical trials (RCTs). The authors of the LAMP2 clinical trial reported in JAMA provide (in eTable 1 in their Supplement) an overview of 27 completed RCTs and 18 ongoing trials of low-dose atropine treatment. What is unique about the LAMP2 trial is its prophylactic rather than therapeutic focus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Methods evaluated include multifocal contact lenses, orthokeratology, and low-dose atropine eyedrops, which have had the most attention in randomized clinical trials (RCTs). The authors of the LAMP2 clinical trial reported in JAMA provide (in eTable 1 in their Supplement) an overview of 27 completed RCTs and 18 ongoing trials of low-dose atropine treatment. What is unique about the LAMP2 trial is its prophylactic rather than therapeutic focus.…”
mentioning
confidence: 99%
“…Adherence to treatment in this trial was assessed by diaries kept by each participant's family. Good adherence was defined as participants receiving their assigned treatment for a weekly average of 5.25 days over the trial's 2-year period and was found to exceed 90% in all 3 groups, with only slight differences by atropine dose (eTable 3 in the Supplement for Yam et al 2 ) not judged to be relevant by the authors. As with any treatment that involves daily administration, and often in this case by a parent, adherence to atropine treatment that is reported in a trial context may well exceed that to be predicted in daily life.…”
mentioning
confidence: 99%
“…Three studies have indicated that nightly administration of low-concentration atropine eyedrops can delay the onset of myopia and/or reduce the shift of refractive error in the myopic direction. [14][15][16] The Low-Concentration Atropine for Myopia Prevention (LAMP2) study 17 reported in this issue of JAMA is the first large-scale, 2-year randomized clinical trial to investigate the effects of nightly administration of 0.05% or 0.01% atropine eyedrops vs placebo eyedrops in children without myopia. The objective of the study was to determine whether low-concentration atropine eyedrops could delay the onset of myopia and reduce the percentage of children who experience a 1.00 D myopic shift in refractive error.…”
mentioning
confidence: 99%
“…The Original Investigation titled “Effect of Low-Concentration Atropine Eyedrops vs Placebo on Myopia Incidence in Children: The LAMP2 Randomized Clinical Trial,” published in the February 14, 2023, issue of JAMA , included an error in Figure 1 that indicated an incorrect number of participants included in the primary outcome analyses in the placebo group, a duplicate reference, and an incorrect funding number. These errors have been corrected online; Figure 1 now indicates the correct number of participants analyzed, the duplicate reference was removed, and the correct funding number is now included in the Funding section.…”
mentioning
confidence: 99%